The Effect of Therapeutic Exercises on Balance, Quality of Life, and Pain in Patients Who Were Receiving Neurotoxic Chemotherapy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Objective The aim of the study was to evaluate the effect of lower limb strengthening and balance exercises on balance, quality of life and neuropathic pain of the cancer patients receiving neurotoxic chemotherapy. Design Patients who were planning to receive neurotoxic chemotherapy agents were included in the first group. They were trained before the neurotoxic chemotherapy sessions with the 10-wk home-based exercise program including lower limb strengthening and balance exercises. The second group of patients who had received the third cycle of neurotoxic chemotherapy had no exercise program. Both groups were evaluated after the third cycle. Neurocom Balance Master and Berg Balance Scale were used to evaluate balance. The neuropathic pain was questioned by PainDETECT questionnaire and the quality of life was assessed with the European Organization for Research and Treatment of Cancer's Quality of Life Questionnaire. Results Sixty patients were admitted to this study. Twenty-four patients were in the exercise group (F = 14, M = 10) and 36 patients were in the control group (F = 17, M = 19). Sociodemographic and clinical data of both groups were similar. Berg Balance Scale (P = 0.005), European Organization for Research and Treatment of Cancer's Quality of Life Questionnaire global quality of life, physical function, and emotional status were higher, and symptom scores and PainDETECT questionnaire score were lower in the exercise group (P < 0.05). Balance tests were different between the groups. Conclusions Strengthening and balance exercises have a valuable effect on balance, quality of life, and neuropathic pain in patients receiving neurotoxic chemotherapy.
Keywords: Balance; Chemotherapy; Neuropathic Pain; Quality of Life; Therapeutic Exercises; INDUCED PERIPHERAL NEUROPATHY; BREAST-CANCER PATIENTS; TURKISH VERSION; PHYSICAL-ACTIVITY; STRENGTH; VALIDITY; RISK; RELIABILITY; PREVENTION; MANAGEMENT